Uncertainty and disciplinary difference: Mapping attitudes towards uncertainty across discipline boundaries. (November 2021) - Dyer, Loren; Power, Jacqueline; Steen, Andrew; Wallis, Louise; Davison, Aidan
Abstract : This article investigates the different ways that uncertainty is understood and approached across design disciplines. Structural attitudes toward uncertainty are assessed in design thinking literature before other possible ways of viewing uncertainty in the design process are introduced. Uncertainty is then presented as a source of epistemological difference between design disciplines, and this difference is explicated through a project that uses literature survey and analytical diagramming to map differences between discipline attitudes to uncertainty. Our review identifies uncertainty as a prevalent source of discipline difference with the goal of better describing barriers, and effective responses to them, in inter- and trans-disciplinary design agendas. Highlights: Literature survey and mapping show discipline difference around design uncertainty. Difference in approaches to design uncertainty may impact interdisciplinary work. Designers need to understand how design uncertainty is valued as well as resolved.